(untitled) (Research, Society and Development, 2021)
Introduction: In Brazil, many women use a postcoital contraceptive method in emergency situations. This method was as effective in preventing pregnancy as the original high-dose estrogen treatment. PURPOSE: to demonstrate the pharmacotherapeutic aspects of self-medication using emergency oral contraceptives. Methods: refers to an exploratory bibliographic research with a qualitative approach, on the importance of pharmaceutical performance in the prevention of self-medication among consumers of the morning-after pill. The searches were carried out from August to November 2021, in the LILACS, SCIELO and PUBMED databases using the controlled descriptors available in DeCS (Descriptors in Health Sciences) and its corresponding MeSH (Medical Subject Headings) in the Portuguese and English languages: “emergency contraceptives”, “adverse effects”, “self-medication” and “morning-after pill”, the English word AND, corresponding to the conjunction E, was used as a Boolean operator, to link the descriptors, for the occurrence simultaneous subject: “emergency contraceptives”, “adverse effects”, “self-medication” and “morning-after pill”. Results: It was identified that emergency contraception is a supportive method to prevent pregnancy and is not routinely used. It may bring undesirable reactions, and the pharmacist is responsible for actions aimed at educating these users in order to avoid self-medication. Conclusion: the use of emergency contraceptives in Brazil, although involved in social, political and religious issues, is extremely important in birth control and the pharmacist has an important role in combating self-medication and in the conscious use of emergency contraceptives.